Good practices of the teacher in Virtual Learning Environments design - Grisales Ruiz, Stefania (Universidad Icesi, 2022)
Several scholars in pedagogical field around the world have established various models or sets of actions that characterize good practices of a teacher in Virtual Learning Environments (VLE) based on a given context. However, this specific collection acts responds to a particular space and time. Therefore, it is not advisable to provide a same set of actions as a generality of success in Virtual Learning Environments due to varied situations faced by both, teacher and learner. Of course, educational institutions around the world are not lagging behind increasingly Virtual Learning Environments emerging concept. A clear example of this is Cali, Valle del Cauca, in 2020, when Icesi University initiated a virtual education system at a graduate level. This University’s wing called Icesi Virtual, among many of its functions, sought teachers’ intervention in their virtual courses design that were within University’s growth plans. Thus, an Icesi Virtual area focused its efforts on accompanying teachers during their Virtual Learning Environment design processin accordance with University’s educational model described in Proyecto Educativo Institucional guidelines (PEI). However, as a consequence of recent creation of this University's wing and virtual education resistance due to lack of knowledge of teaching methods and techniques based on this modality, Icesi Virtual had not yet achieved greater prominence.
Keywords: Entornos virtuales de aprendizaje; Sistematización de experiencias; Experiencias educativas; Aprendizaje significativo; Educación virtual; Práctica educativa; Trabajos de grado; Departamento de Pedagogía; Licenciatura en Lenguas Extranjeras con énfasis en inglés